Generation of efficient 20 GHz optical combs in a Brillouin-erbium fiber laser - Parvizi, R.; Shahabuddin, N.S.; Ali, N.M.; Harun, Sulaiman Wadi; Emami, S.D.; Vaseghi, B.; Ahmad, Harith (IOP Publishing, 2013)
A tunable multiwavelength Brillouin-erbium fiber laser is experimentally demonstrated with a double-Brillouin-frequency spacing. This double-frequency shifter is constructed by incorporating a four-port circulator to isolate and circulate the odd-Stokes signals through the 10?km long non-zero dispersion shifted fiber, which acts as a Brillouin gain medium. The output even-order Stokes signals are amplified in the erbium gain block formed in a ring cavity. Up to 15 lasing lines with a wavelength spacing of 0.173?nm have been achieved at a 980?nm pump power of 50?mW and a Brillouin pump of 3?dB?m. The multiwavelength laser source exhibits a 10?nm tuning range from 1552 to 1562?nm with the optical signal-to-noise ratio of the desired output channels at around 34.5?dB.